Quantum optics an introduction - Fox, Mark (Oxford Oxford University Press, 2006)
Quantum Optics: An Introduction Book Description About the Book :- Most previous texts on quantum optics have been written primarily for the graduate student market at PhD level and above. Quantum optics: an introduction aims to introduce a wide range of topics at a lower level suitable for advanced undergraduate and Masters level students in physics. The text is divided into four main parts, covering modern topics in both pure and applied quantum optics: I. Introduction and background material. II. Photons. III. Atom-photon interactions. IV. Quantum information processing. The emphasis of the subject development is on intuitive physical understanding rather than mathematical arguments, although many derivations are included where appropriate. The text includes numerous illustrations, with a particular emphasis on the experimental observations of quantum optical phenomena. Each chapter includes worked examples, together with 10-15 exercises with solutions. Six appendices are included to supplement the main subject material. Contents :- Part I: Introduction and Background 1. Introduction 2. Classical Optics 3. Quantum Mechanics 4. Radiative Transitions in Atoms Part II: Photons 5. Photon Statistics 6. Photon Antibunching 7. Coherent States and Squeezed Light 8. Photon Number States Part III: Atom--Photon Interactions 9. Resonant Light--Atom Interactions 10. Atoms in Cavities 11. Cold Atoms Part IV: Quantum Information Processing 12. Quantum Cryptography 13. Quantum Computing 14. Entangled States and Quantum Teleportation Appendices A. Poisson Statistics B. Parametric Amplification C. The Density of States D. Low Dimensional Semiconductor Structures E. Nuclear Magnetic Resonance F. Bose--Einstein Condensation About the Author :- Prof. Mark Fox , is a Professor of Physics in the Department of Physics and Astronomy at the University of Sheffield.
Keywords: Quantum optics